2018
DOI: 10.1021/acs.nanolett.8b04643
|View full text |Cite
|
Sign up to set email alerts
|

InGaAs–GaAs Nanowire Avalanche Photodiodes Toward Single-Photon Detection in Free-Running Mode

Abstract: Single photon detection at near-infrared (NIR) wavelengths is critical for light detection and ranging (LiDAR) systems used in imaging technologies such as autonomous vehicle trackers and atmospheric remote sensing. Portable, high-performance LiDAR relies on silicon-based singlephoton avalanche diodes (SPADs) due to their extremely low dark count rate (DCR) and afterpulsing probability, but their operation wavelengths are typically limited up to 905 nm. Although InGaAs-InP SPADs offer an alternative platform t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 51 publications
2
56
0
Order By: Relevance
“…Linear mode APDs have been reported in ensemble InGaAs/GaAs core-shell nanoneedles [91], exhibiting extremely high gain values at bias voltages significantly below breakdown [92] due to the reduction of active material volume. More significantly, a vertical InGaAs/GaAs nanowire array separate absorption-multiplication (SAM) APD operating in Geiger mode has also been demonstrated recently [93]. The nanowire array contained thousands of nanowires with each avalanche event confined in a single nanowire, drastically reducing the avalanche volume and the number of filled traps.…”
Section: Junction Based Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linear mode APDs have been reported in ensemble InGaAs/GaAs core-shell nanoneedles [91], exhibiting extremely high gain values at bias voltages significantly below breakdown [92] due to the reduction of active material volume. More significantly, a vertical InGaAs/GaAs nanowire array separate absorption-multiplication (SAM) APD operating in Geiger mode has also been demonstrated recently [93]. The nanowire array contained thousands of nanowires with each avalanche event confined in a single nanowire, drastically reducing the avalanche volume and the number of filled traps.…”
Section: Junction Based Photodetectorsmentioning
confidence: 99%
“…The nanowire array contained thousands of nanowires with each avalanche event confined in a single nanowire, drastically reducing the avalanche volume and the number of filled traps. This led to an extremely small afterpulsing probability compared with conventional InGaAs-based single-photon avalanche diodes (SPADs) and enabled operation in free-running mode up to 150 K, which is attractive for emerging integrated photonics and quantum information applications [93].…”
Section: Junction Based Photodetectorsmentioning
confidence: 99%
“…1D core‐shell heterojunction nanostructures have great potential for high‐performance compact optoelectronic devices owing to their high interface area‐to‐volume ratio . To date, core‐shell heterostructure nanowire systems, such as InAs/AlSb, InGaAs‐GaAs, ZnO/CuCrO 2 , and GaN/AlN, with outstanding performance as photodetectors have been reported . For example, β‐Ga 2 O 3 is an excellent candidate for solar‐blind photodetection, with a direct wide bandgap of ~ 4.9 eV (253 nm).…”
Section: Nanowire Photodetectorsmentioning
confidence: 99%
“…152 To date, core-shell heterostructure nanowire systems, such as InAs/AlSb, InGaAs-GaAs, ZnO/CuCrO 2 , and GaN/AlN, with outstanding performance as photodetectors have been reported. [153][154][155][156] For example, β-Ga 2 O 3 is an excellent candidate for solarblind photodetection, with a direct wide bandgap of 4.9 eV (253 nm). Most β-Ga 2 O 3 nanostructure-based photodetectors are photoconductive with a relatively slow response speed due to the persistent photoconductivity effect.…”
Section: Nanowire Photodetectorsmentioning
confidence: 99%
“…Recently GaAs-based nanowire APDs and SPADs have been demonstrated experimentally with impressive properties including large lattice mismatch accommodation, low dark current and high avalanche gain in the near infrared regime [8], [9] due to its very small active volume compared to its planar counterpart. For instance, Senanayake et al reported a GaAs nanowire APD [8] with high avalanche gain above 100.…”
Section: Introductionmentioning
confidence: 99%